Portal vein septic thrombosis secondary to complicated appendicitis: Case report - Jacqueline Vasconcelos Quaresma; Igor Mizael da Costa Saadi; Rafael José Romero Garcia; Leanne Isadora Vasconcelos Quaresma (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Background: Portal vein septic thrombophlebitis is a rare and serious event of late diagnosis and secondary to intra-abdominal infection.  Case report: A 21-year-old man was admitted to the hospital with loss of weight, fever, chills, hepatosplenomegaly, and history of abdominal pain in the right iliac fossa previously treated with ciprofloxacin. At the entrance physical examination, he was emaciated and had no signs of abdominal pain upon palpation. Computed tomography showed portal vein thrombosis and nodular image in the ileocecal region, initiating antibiotic therapy. After exploratory laparotomy, appendicitis was confirmed and hepatic collections were found. After ten days of the procedure and the end of the antibiotic therapy, he was discharged, keeping well and without complaints.  Conclusions: Septic thrombophlebitis is a rare but serious complication of non-specific signs and symptoms, making diagnosis difficult. Imaging tests are necessary that show the thrombosis to close diagnosis. Treatment should be started early, with the introduction of antibiotics and eradication of the septic focus.